how do you figure this equation step by step

4x-3y=11
2x+3y=13

1 answer

from eg 2 you get
3y=13-2x
you should subsitute it i eq 1

4x-(13-2x)=11
4x-13+2x=11

6x-13=11
6x=24
divid the eq by 6
we get x=4

the put x=4 in
3y=13-2x
3y = 13 -2*4
3y=5
y =5/3
Similar Questions
  1. JamalStep 1: Set equation =0 . x2+4x−12=0 Step 2: Write quadratic equation as the product of two factors. (x+6)(x−2)=0 Step
    1. answers icon 2 answers
    1. answers icon 1 answer
  2. Josephine solved a quadratic equation: (x+6)^2=49. Her work is shown below.Step 1: √(x+6)^2 = √49 Step 2: x+6 = 7 Step 3: x
    1. answers icon 2 answers
  3. Consider the sequence of steps to solve the equation:5(x - 3) = 7x2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3
    1. answers icon 3 answers
more similar questions